International equity flows and returns: a quantative equilibrium approach - Rui Albuquerque; Gregory H. Bauer; Martin Schneider (European Central Bank (ECB), 2004)
This paper considers the role of foreign investors in developed-country equity markets. It presents a quantitative model of trading that is built around two new assumptions: (i) both the foreign and domestic investor populations contain investors of different sophistication, and (ii) investor sophistication matters for performance in both public equity and private investment opportunities. The model delivers a unified explanation for three stylized facts about US investors' international equity trades: (i ) trading by US investors occurs in bursts of simultaneous buying and selling, (ii ) Americans build and unwind foreign equity positions gradually and (iii ) US investors increase their market share in a country when stock prices there have recently been rising. The results suggest that heterogeneity within the foreign investor population is much more important than heterogeneity of investors across countries.
Keywords: F30; G12; G14; G15; 330; asset pricing; Asymmetric information; heterogenous investors; international